Different Methods of Teaching the English Language - Nilufar Karimovna Otamurodova (Euro Asian Journal Publishing, 2023)
This article is about interactive learning - a modern way of learning, which consists in the interaction of all participants in the educational process: teachers and students. Today, this method of teaching is widely used everywhere: in schools, universities, courses and trainings, because this technique is extremely effective not only in terms of gaining knowledge, but also in terms of the formation of personal skills and the development of the character of students. It is important that interactive teaching methods can be applied to almost all types of training: in personal meetings in groups, on the Internet, by telephone. The article also examined the involvement of students in interactive activities in English classes. Incredible results can be obtained by interactively learning foreign languages
Keywords: discussion; debate; problem-based learning